The right to participate in the management of state affairs in the conditions of digitalisation: theory and practice - Maslovskaya, Tatiana S.; Kisialiova, Tatsiana M. (Journal of the Belarusian State University. Law, 2022)
The authors of the article reveal the essence and features of the realisation of the right to manage the affairs of the state in the conditions of digitalisation of the state and society. The authors substantiate the need to improve the institutions of public discussion of draft acts, initiating the adoption of regulatory legal acts, electronic appeals, taking into account the needs and capabilities of citizens in the feld of information technology use.